Pengaruh Inflasi dan Suku Bunga Terhadap Pertumbuhan Ekonomi di Provinsi Kalimantan Selatan Tahun 2018-2022 - Hushila Rizqiani Awalia; Mukhlis Kaspul Anwar; Muhammad Arief; Lisda Aisyah; Nur Habibah (Program Studi Ekonomi Syariah IAI Darul Ulum Kandangan, 2024)
Abstract Inflation is a continual increase in the purchase price of products and services. Purpose of this research is to identify how much influence inflation and interest rates have on economic growth in South Kalimantan Province. The data used are secondary data in the form of time series data including data on inflation, interest rates, and economic growth in South Kalimantan province for the period 2018-2022. Quantitative descriptive methods were used to conduct this research. It uses Multiple Linear regression analysis methods, and data processing using Eviews 12 software. The findings of this research are that inflation has no significant effect on the economic growth of South Kalimantan Province, and also interest rates have no significant effect on the economic growth of South Kalimantan Province. Then together inflation and interest rates also have no significant effect on the economic growth of South Kalimantan Province with an R-squared value of 0.636702 or 36.3%. Keywords : Economic Growth, Inflation, Interest Rates, BI Rate